Social information processing, experiences of aggression in social contexts, and aggressive behavior in adolescents - Lösel, Friedrich; Bliesener, Thomas; Bender, Doris (Criminal Justice and Behavior, 2007)
This study examines social information processing and experiences of aggression in social contexts as predictors of different forms of aggressive behavior. A sample of 102 boys (aggressive, average, competent, and victimized students) was investigated with a prospective design in Grade 7/8 and again in Grade 9/10. Results show an aggressive-impulsive response repertoire strongly predicted self-reported and teacher-reported physical aggression, verbal aggression, violent offenses, general aggression, and other forms of delinquency. Positive evaluations of aggressive responses showed a weaker effect, and attributions of hostility and aggressive/egocentric goal setting had no impact. Perceived aggression in the family, in the peer group, in media consumption, and (less consistently) at school predicted verbal aggression as well as physical aggression and violent offenses. Multivariate analyses revealed both mediating and independent effects of social information processing and experiences of aggression in social contexts. Results are discussed from methodological and theoretical perspectives.
Keywords: social information processing; aggression; juvenile delinquency; social learning